Nano biosensors: Classification, electrochemistry, nanostructures, and optical properties - Ahmed Mahdi Rheima; Zainab T. Al-Sharify; Ameen Alwan Mohaimeed; Mustafa Abd Al- Hussein Kazem; Jameel M Dhabab; Duaa Mohammed Athair; Tomy Muringayil Joseph; Debarshi Kar Mahapatra; Sabu Thomas; Ehsan Kianfar (Results in Engineering, 2024)
The incidence of chronic diseases in contemporary society has been steadily rising with the ageing population. They place a significant strain on both people and the healthcare system, and they are the leading cause of death. As a result, novel detection methods that allow for early identification of chronic diseases to manage therapy are in high demand. Modern sensing tools have emerged in the form of biosensors, which can detect biomarkers and transform them into quantifiable signals. The fields of environmental science, agriculture, drug discovery, biotechnology, food safety, and medical diagnostics might all benefit from the data they provide. The development of more precise, sensitive, and selective diagnostic tools is, nevertheless, of the utmost importance, as is the ability to identify biomarkers as disease indicators at very low concentrations. Nano biosensors are a new generation of analytical instruments that have evolved from the integration of nanomaterials with biosensors. One promising option for continuous, real-time health monitoring is nanostructured biosensors, which provide exceptional sensitivity, selectivity, and reproducibility. Nano biosensors are categorized in this extensive study according to their size, production process, and transduction mechanism. Also, talk about the latest developments and uses for nano biosensors, and cover some important elements of them, focusing on their electrochemistry and optical characteristics. Further research is needed to fully understand nano biosensors and their potential as a tool for personalized treatment, since there are still many unknowns about their biocompatibility, toxicity, stability, and integration into the human body.